Pendugaan Struktur Bawah Permukaan Daerah Buton Utara Provinsi Sulawesi Tenggara Berdasarkan Data Anomali Grvitasi Lokal Citra Satelit GGMplus - Asniar Asniar; Jamhir Safani; Suryawan Asfar (Jurnal Rekayasa Geofisika Indonesia, 2020)
It has now expanded data measuring the gravitational field of high-resolution satellite imagery and the spacing between the measurement point 220 meters namely gravity satellite imagery GGMplus ( Global Gravity Model plus ). GGMplus provides gravity data that covers the entire continent including the coastal zone, so it is better in determining subsurface structures. Research using GGMplus satellite imagery, has been carried out in North Buton, Southeast Sulawesi Province find out anomaly distribution patterns and subsurface structure modeling. The data used in the form of gravity disturbance data which is free air anomaly data, and then only needs to be corrected Bouguer and Terrain Correction to get a complete Bouguer anomaly. Then a flat plane projection is carried out, upward continuation and modeling. The results of Bouguer anomaly resulting from upward continuation show anomaly distribution patterns from north northwest to southeast. This is relatively the same as the direction of the structure in the study area. Based on the results of modeling on the local anomaly in the A-A'trajectory, it is suspected that the smoothness of the Doole formation with a density value of 2.7-2.9 gr/m3in the southeast east direction and a large enough rock body that causes anomaly in that direction is relatively very high. Whereas on the B-B trajectory it was found that a fault was a descending fault in the north-northeast where the Ogena formation with a density of 2.0 -2.55 gr/cm3 wasraised to a depth of ±100 meters and then was crushed by the Tobelo formation with a density value of 1.96-2.2 gr/m3.